Clinical usefulness of narrow band imaging magnifying colonoscopy for assessing ulcerative colitis-associated cancer/dysplasia - Nishiyama, Soki; Oka, Shiro; Tanaka, Shinji; Sagami, Shintaro; Hayashi, Ryohei; Ueno, Yoshitaka; Arihiro, Koji; Chayama, Kazuaki (Endoscopy International Open, 2016)
Background and study aims: Colitis-associated cancer/dysplasia (CC/D) can affect the life expectancy of patients with ulcerative colitis (UC). Although the utility of magnifying chromocolonoscopy has been shown, the use of optical magnification with narrow band imaging (NBI) for distinguishing CC/D from non-neoplastic lesions in patients with UC has not been reported. We evaluated whether endoscopic findings are distinguishing and thus assessed the clinical usefulness of NBI magnification for differentiating UC-associated lesions.Patients and methods: The study involved 27 patients diagnosed and treated at Hiroshima University Hospital between September 2005 and March 2015: a neoplasia group (16 lesions) and a non-neoplasia group (17 lesions). The neoplasias comprised 9 dysplastic lesions, 5 intramucosal carcinomas, and 2 submucosal carcinomas, and 17 non-neoplastic lesions. Targeted biopsy samples of suspicious lesions detected by conventional colonoscopy were classified pathologically as neoplastic or non-neoplastic, and NBI magnifying colonoscopy findings (i. e., the surface [unclear/regular/irregular/amorphous] and vascular [same as the background mucosa/regular/irregular/avascular] patterns) of the 2 lesion types were compared.Results: Irregular/amorphous surface patterns were significantly more common in neoplastic lesions than in non-neoplastic lesions (81 % [13/16] vs. 18 % [3/17], respectively, P < 0.001). Irregular/avascular vessel pattern tended to be more common in neoplastic lesions (75 % [12/16] vs. 41 % [7/17], respectively). The surface pattern correctly predicted 82 % of neoplastic lesions, and the vessel pattern correctly predicted 67 % of non-neoplastic lesions. The 2 endoscopic findings together correctly predicted 91 % of neoplastic lesions.Conclusion: Surface pattern, determined by magnifying colonoscopy with NBI, is useful for differenting between UC-associated neoplastic and non-neoplastic lesions.